ASSESSMENT OF LEARNING FOR INFORMATION LITERATION COURSE USING THE SOCRATIVE APPLICATION - Inawati, Inawati; Desyana, Nidya (Program Pascasarjana, UIN Alauddin Makassar, 2020)
The era of industrial revolution 4.0 is marked by the development of very fast and unlimited information so that education has a very important role. Along with these developments, it is necessary to develop a new paradigm in the world of education, namely using a touch of technology in carrying out learning assessments, one application that can be used is the Socrative application which can be used by teachers in providing feedback on student work. The purpose of this study was to describe the practicality of using the Socrative application as a media assessment of learning in the Information Literacy course with 18 students as respondents. The average percentage result of all indicators during the trial period was 58.8% who considered it feasible and practical to use the Socritive application when carrying out the assessment of learning.